2019
DOI: 10.1111/and.13468
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the protective effect of aerobic exercise on oxidative stress and histological damages of testicular tissue associated with chlorpyrifos in male rats

Abstract: The current study aimed to investigate the protective effects of moderate aerobic exercise against chlorpyrifos (CPF)‐induced testes dysfunction. In excremental study, 48 adult male albino rats were randomly allocated into 16 groups of 3 rats each. Twelve experimental groups received intraperitoneal injection (5 days a week) of either 1.0 or 3.0 mg/kg body weight CPF in DMSO for 2, 4 or 6 consecutive weeks. Seven of these experimental groups were subjected to run at moderate exercise intensity for 5 days per w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The study by Nikbin et al also showed that aerobic activity in chlorpyrifos (CPF)-injected rats increased SOD activity in two weeks of activity, but in the fourth and sixth weeks, SOD activity decreased in the CPF-injected groups or groups without aerobic activity. Also, MDA-induced lipid peroxidation in testicular tissue improved with training in the CPF-injected group, which was not statistically significant ( 32 ). Overall, the results of this study, as in the present study, did not show significant improvement for most CPF-induced injuries in trained rats.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study by Nikbin et al also showed that aerobic activity in chlorpyrifos (CPF)-injected rats increased SOD activity in two weeks of activity, but in the fourth and sixth weeks, SOD activity decreased in the CPF-injected groups or groups without aerobic activity. Also, MDA-induced lipid peroxidation in testicular tissue improved with training in the CPF-injected group, which was not statistically significant ( 32 ). Overall, the results of this study, as in the present study, did not show significant improvement for most CPF-induced injuries in trained rats.…”
Section: Discussionmentioning
confidence: 97%
“…The interactive effects of HIIT and Crocin consumption on oxidant / antioxidant redox balance have also been investigated in the heart and liver tissue of DOX-treated rats, indicating favorable interactions on decreasing MDA and increasing CAT and SOD ( 32 , 33 ). This study showed for the first time that concurrent Crocin supplementation, especially at a dose of 50 mg/kg/d and HIIT training, with a synergistic effect, improves antioxidant defense indicators and reduces oxidative pressure in the testicular tissue of rats.…”
Section: Discussionmentioning
confidence: 99%